2014
DOI: 10.1002/ange.201406905
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐Oxidative Coupling of Glycine Derivatives

Abstract: The unprecedented title reaction between glycine derivatives and indoles, as well as the auto-oxidative Povarov/ aromatization tandem reaction of glycine derivatives with olefins are described. The reactions were performed in the absence of redox-active catalysts and chemical oxidants under mild reaction conditions. Only simple organic solvents and air (or O 2 ) were required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 72 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…We questioned if the substrates secondary amines were replaced with secondary hydrazines, as shown in Scheme , the method has the potential to produce triazine derivatives through [3+3] manner or N ‐amino imidazolidine derivatives through [2+3] manner. Based on our experience in oxidative dehydrogenative cyclization, we think benzylhydrazines could be chosen instead of the corresponding secondary amines because benzyl position of benzylhydrazine derivatives may be easily oxidized to generate carbocations for further transformation. And Carbobenzyloxy (Cbz) could be selected as protecting group because: (1) It will improve the tolerance of hydrazine motif under oxidation conditions; (2) It will differentiate two hydrazine N atoms' nucleophilic ability; (3) It is easy to be removed.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…We questioned if the substrates secondary amines were replaced with secondary hydrazines, as shown in Scheme , the method has the potential to produce triazine derivatives through [3+3] manner or N ‐amino imidazolidine derivatives through [2+3] manner. Based on our experience in oxidative dehydrogenative cyclization, we think benzylhydrazines could be chosen instead of the corresponding secondary amines because benzyl position of benzylhydrazine derivatives may be easily oxidized to generate carbocations for further transformation. And Carbobenzyloxy (Cbz) could be selected as protecting group because: (1) It will improve the tolerance of hydrazine motif under oxidation conditions; (2) It will differentiate two hydrazine N atoms' nucleophilic ability; (3) It is easy to be removed.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The utilization of Au(I) (AuCl, PPh 3 AuCl, ( t‐ BuC 6 H 4 O) 3 PAuCl, JohnPhosAuCl, JohnPhosAuMe) resulted in the formation of the product with low yields except for (PhO) 3 PAuCl (Table , entries 24–29). Among the solvents examined, EtOH was the most effective (Table , entries 30–34), DCE was not crucial for the reaction yield as reported in auto‐oxidation reactions . Further studies indicated that reducing the catalyst loading of 8b to 5% had little impact at the reaction outcome (Table , entry 34).…”
Section: Resultsmentioning
confidence: 94%
“…Since the first one‐pot Povarov reaction reported by García Mancheño using FeCl 3 as the catalyst and a 2,2,6,6‐tetramethyl‐1‐piperidinyloxy (TEMPO) oxoammonium salt as the oxidant in 2011, similar catalytic systems have also been developed in other reactions . In 2014, Huo reported the auto‐oxidative coupling of glycine (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, aliphatic amines can be oxidized by O 2 but only with the assistance of light in the presence of photosensitizer. [15,17,21] In as imilar manner to the photochemical processes, [15,22] the O 2 -mediated SET process initially generates the aminium radical 10 k and superoxide ion (Scheme 4). Theaminium radical 10 k then undergoes decarboxylation to form the a-amino radical 11 k,which is oxidized to produce the iminium ion 7k with concurrent production of H 2 O 2 .…”
Section: Angewandte Chemiementioning
confidence: 99%